The Application of Acoustic Emission Technique to Monitor the Early Setting Process of Cement Pastes - Hoduláková, Michaela; Topolář, Libor; Kucharczyková, Barbara (EDP Sciences, 2019)
The obtained physico-mechanical properties (mainly flexural and compressive strength) of cement-based composite materials depend on various factors (type of mixture, its composition, standard hardening process, proper testing, handling during transportation, etc.). Important properties to be tested include in particular properties of materials in the fresh, still plastic, state, since accurate identification of defects in building materials/structures at the early stage will allow early elimination and minimization of their future consequences. The aim of this paper is the application of the acoustic emission (AE) method for the detection of high-frequency elastic waves created by physical and chemical processes accompanying setting and hardening of cement pastes. The experiment was conducted on cement pastes produced from different cements but with the same water/cement ratio. Since there are many possible sources of AE and the identification of the individual sources is difficult, the monitoring of the setting cement paste was conducted simultaneously with measurements of the internal temperature. The results of these experiments can be used to expand the understanding of the various processes occurring at the early stage of setting and hardening of cement-based materials.

The obtained physico-mechanical properties (mainly flexural and compressive strength) of cement-based composite materials depend on various factors (type of mixture, its composition, standard hardening process, proper testing, handling during transportation, etc.). Important properties to be tested include in particular properties of materials in the fresh, still plastic, state, since accurate identification of defects in building materials/structures at the early stage will allow early elimination and minimization of their future consequences. The aim of this paper is the application of the acoustic emission (AE) method for the detection of high-frequency elastic waves created by physical and chemical processes accompanying setting and hardening of cement pastes. The experiment was conducted on cement pastes produced from different cements but with the same water/cement ratio. Since there are many possible sources of AE and the identification of the individual sources is difficult, the monitoring of the setting cement paste was conducted simultaneously with measurements of the internal temperature. The results of these experiments can be used to expand the understanding of the various processes occurring at the early stage of setting and hardening of cement-based materials.
The Application of Acoustic Emission Technique to Monitor the Early Setting Process of Cement Pastes
Keywords: acoustic emission; early hydration process; fine-grained cement composites; NDT; acoustic emission; early hydration process; fine-grained cement composites; NDT